Patria and Mother Patria. The centenary holidays between 1910 and 1911 in Tunja - Martínez Martín, Abel Fernando; Otálora Cascante, Andrés Ricardo (Universidad Pedagógica y Tecnológica de Colombia, 2012)
The current article aims at describing the holidays of the National Independence Centenary (1900) and the proclamation of Tunja’s Constitution (1911) within theframe of the centenaries decade (1910-1919) carried out in Tunja, and seen since the celebrations of the bicentenaries. These celebrations through which the Boyacá Department social elite, such as the Government House and Dioceses articulated a process re-conciliating the new nation with the old metropolis, regarding thediscourse and the public holiday through Tunja’s center of history (1905) and the patriotic history in the pursuit of progress, modernity and the peace of the “Boyacensetown”, historical construction that was seeking the creation of a political community appealing to the national memory. A systematic search was carried out in order todevelop this work by means of the regional, national and press iles since the beginning of the twentieth century.